Perlindungan Hukum dalam Kegiatan Investasi Bagi Pemilik Modal di Kota Jambi - Resi Indah Sari; Nelli Herlina (Universitas Jambi, Fakultas Hukum, 2020)
This article discusses about the legal protection of capital owners in the investment activities in Jambi City which is based on the regional regulation of Jambi city as well as obstacles faced by investment actors in the implementation of capital investment in Jambi City. This discussion is necessary because the development of investmentin the city of Jambi is increasing in line with the development of the time in line with the law number 25 in 2007 on investment that was formed as the basis of consideration is to accelerate the development of national economy and realize Indonesia's political and economic sovereignty. This research is using juridical research method empirical with results that shows the legal protection of capital owners in investment activities has been supported through the Department of Investment and Integrated services Jambi to facilitate the owner of capital in obtaining business licenses. Constraints encountered by capital owners in the activities of capital keeping in Jambi city caused by the number of licensing requirements that must be fulfilled by the capital owner to start the business and Online Single Submission (OSS) system that has not been carried out with maximum because the owner of the capital remains to carry out the licensing manually and independently to the government agencies authorized to issue operational licenses of the company. Keywords: Legal; Protection; Investment; Abstrak Artikel ini membahas bagaimana perlindungan hukum terhadap pemilik modal dalam kegiatan investasi di Kota Jambi yang didasarkan pada Peraturan Daerah Kota Jambi serta kendala yang dihadapi pelaku investasi dalam pelaksanaan kegiatan penanaman modal di Kota Jambi. Pembahasan ini diperlukan karena perkembangan iklim investasi di Kota Jambi yang semakin meningkat sejalan dengan perkembangan zaman sejalan dengan Undang-Undang Nomor 25 Tahun 2007 tentang Penanaman Modal yang dibentuk sebagai dasar pertimbangan yaitu untuk mempercepat pembangunan ekonomi nasional dan mewujudkan kedaulatan politik dan ekonomi Indonesia. Penelitian ini menggunakan metode penelitian yuridis empiris dengan hasil yang menunjukan perlindungan hukum terhadap pemilik modal dalam kegiatan investasi telah di tunjang melalui Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Jambi untuk memudahkan pemilik modal dalam memperoleh izin usaha. Kendala yang ditemui pemilik modal dalam kegiatan penaman modal di Kota Jambi disebabkan banyaknya persyaratan perizinan yang harus dipenuhi oleh pemilik modal untuk memulai usaha serta sistem Online Single Submission (OSS) yang belum terlaksana dengan maksimal karena pemilik modal tetap harus melakukan perizinan secara manual dan tersendiri ke instansi pemerintah yang berwenang dalam mengeluarkan izin operasional perusahaan. Kata kunci: Perlindungan; Hukum; Investasi